2022
DOI: 10.3389/fsurg.2022.905049
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa and microbiota – the role of intrinsic parameters on intestinal wound healing

Abstract: Mucosal healing in the gut is an essential process when it comes to chronic inflammatory disorders such as inflammatory bowel diseases (IBD) but also to the creation of intestinal anastomosis. Despite an improvement of surgical techniques, the rates of anastomotic leakage remain substantial and represent a significant health-care and socio-economic burden. Recent research has focused on intrinsic factors such as mucosal linings and differences in the intestinal microbiota and identified specific endoluminal ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the current work we demonstrated that various lactobacilli release large amounts of ligands that can specifically activate FPR2 and possibly mediate their probiotic effects. We found that among the strongest FPR2 activators are lactobacilli that were reported to promote wound healing and prevent inflammation in the gut (Kelm and Anger 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the current work we demonstrated that various lactobacilli release large amounts of ligands that can specifically activate FPR2 and possibly mediate their probiotic effects. We found that among the strongest FPR2 activators are lactobacilli that were reported to promote wound healing and prevent inflammation in the gut (Kelm and Anger 2022).…”
Section: Discussionmentioning
confidence: 99%
“…FODMAP foods are assumed to aggravate the gut leakage, however, there are no scientific evidences available. In addition, bacteria such as aerotolerant lactobacilli or wound-associated Akkermansia muciniphila might be critical for wound and anastomotic healing in the gut [82]. Moreover, kinase inhibiting drugs like ruxolitinib were found to alleviate inflammation, apoptosis, and intestinal barrier leakage in UC via STAT3 [83].…”
Section: Current Treatment Strategiesmentioning
confidence: 99%
“…This, together with the fact that the products derived from bacteria can regulate the production and secretion of mucin, thus promoting the loss of the integrity of the epithelial barrier ( Figure 1 ). Lastly, epithelial repair is known to be altered in IBD and this is reflected in the creation of aberrant intestinal anastomosis after a bowel resection, giving rise to the recurrence of the disease in the same place ( Kelm and Anger, 2022 ).…”
Section: A Brief Outline Of the Epithelial Barrier Role In The Pathop...mentioning
confidence: 99%